Natación artística en niñas: antropometría, genotipo y rendimiento deportivo - Romero-Lorca, A.; de la Calle, L.; Novillo, A.; Fernández-Santander, A.; Blanco, M.A.; Rodelgo, T.; Andreu-Vázquez, C.; Gaibar, M. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2022)
In sport, optimizing weight and body composition is important for performance although an excessive drive for thinness can lead to diminished performance and health problems. This is especially important in the youngest athletes. This study examines 60 national competition-level Spanish artistic swimmers aged 9-17 years. Participants were divided into 3 categories: 12 years and under, 13-15 and 16-17 years. The data analysed were anthropometric measures, menarche age, genotype related to performance (gene ACTN3) and athletic performance. Relationships between athletic performance and anthropometric or genetic data were compared among the three age groups.